HUMAN RESOURCE DEVELOPMENT STRATEGIES AND THEIR CONTRIBUTION TO SUSTAINABLE PERFORMANCE IN LAW ENFORCEMENT AGENCIES - Bahagia Dachi; Oscarius Yudhi Ari Wijaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Human resource development strategies are central to sustaining organizational performance in law enforcement agencies where human capital, professional competence, and institutional legitimacy are paramount. This literature-review synthesizes empirical and applied studies published between 2015 and 2025 to identify HRD approaches that contribute to sustainable performance outcomes in policing. The review emphasizes training and continuous learning, competency-based development, talent management and succession planning, performance management linked to career pathways, wellbeing and resilience programs, and technology-enabled learning. Evidence indicates that integrated HRD strategies that align training with competency frameworks, embed learning in career progression, and support officer wellbeing are associated with improved operational performance, lower attrition, higher professional standards, and greater public trust (Piwowar-Sulej, 2023; Nababan, 2025; Maphosa, Shumba & Mutasa, 2021). However, transferability of training to field practice, resource constraints, weak supervisory capacity, and lack of evaluation frameworks limit sustained impact. The review highlights implementation principles for sustainable HRD: alignment with organizational strategy, managerial and supervisory capability building, transparent talent pipelines, continuous monitoring and evaluation, and investments in officer wellbeing and digital learning infrastructures. The paper ends with a research agenda calling for longitudinal program evaluations, comparative studies across jurisdictions, and mixed-methods work that links HRD interventions to community-level performance indicators. Keywords: human resource development, policing, sustainable performance, talent management